Presurgical diagnostic difficulties in an asymptomatic patient with primary transitional cell carcinoma of the oviduct: case report - Abdalla, Nabil; Wnuk, Anna; Trojanowski, Seweryn; Jakimiuk, Alicja; Stanirowski, Pawel; Cendrowski, Krzysztof; Sawicki, Wlodzimierz (Menopause Review/Przegląd Menopauzalny, 2018)
Primary transitional cell carcinoma of the fallopian tube is a very rare condition. We present a case of a 70-year-old asymptomatic Caucasian patient with an irregular solid right adnexal mass of 67  35  59 mm which was discovered during routine ultrasound pelvic examination. There was no acoustic shadow and the patient did not feel pain during examination. No evidence of metastases or ascites was found by ultrasound. There was moderate vascularization of the mass. The mass was considered malignant according to the subjective assessment of the examiner. Serum level of CA125 was elevated to 519 U/ml. The results of logistic regression model LR2 according to the International Ovarian Tumor Analysis (IOTA) group was 64.4%, suggesting the malignant nature of the mass. The IOTA-ADNEX model showed 97% probability of malignancy, probably (85.5%) stage II-IV ovarian cancer. The risk of malignancy being borderline, stage I and metastatic was 0.6%, 3.9% and 7%, respectively. Omitting CA125 in the IOTA-ADNEX model slightly decreased the probability of malignancy to 81.3%, still most likely (54.2%) stage II-IV ovarian cancer. The results of risk of malignancy indices RMI I-IV were 1557, 2076, 1557 and 2076, respectively, reflecting the malignant nature of the mass. The final diagnosis was transitional cell carcinoma of the fallopian tube, stage IIIc according to FIGO.